Facial Modeling for Interactive 3D Reconstruction in Web Applications - Silva, Josivan Pereira da; Costa, Geiza Caruline; Melo, João; Mascarenhas, Iann Vicari; Kurashima, Celso Setsuo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
A recent kind of Web application incorporates three-dimensional image content, which allows interactivity and new visual experiences to the users. However, rendering 3D video content has been a research challenge due to modeling complexity and visual content definition. This paper proposes an interactive Web application that shows 3D modeled human faces that were captured by depth cameras, and using HTML5 and JavaScript resources for 3D reconstruction and interactivity. The 3D modeling process is realized with a triangulation algorithm called Convex Hull. We propose a method that divides the model into four parts in order to achieve improvements on visual details around the concave areas. The final model mesh is saved into an XML file, which is readable by any Web browser. The implemented viewer resulted in image visual enhancements, simple synchronized integration of video and audio content, and friendly interactivity capabilities.